Preschool Television Viewing and Adolescent Test Scores: Historical Evidence from the Coleman Study* - Gentzkow, Matthew; Shapiro, Jesse M. (Quarterly Journal of Economics, 2008)
We use heterogeneity in the timing of television's introduction to different local markets to identify the effect of preschool television exposure on standardized test scores during adolescence. Our preferred point estimate indicates that an additional year of preschool television exposure raises average adolescent test scores by about 0.02 standard deviations. We are able to reject negative effects larger than about 0.03 standard deviations per year of television exposure. For reading and general knowledge scores, the positive effects we find are marginally statistically significant, and these effects are largest for children from households where English is not the primary language, for children whose mothers have less than a high school education, and for nonwhite children.